Islet Transplantation for Brittle Type 1 Diabetes: The UIC Protocol - Gangemi, A.; Salehi, P.; Hatipoglu, B.; Martellotto, J.; Barbaro, B.; Kuechle, J. B.; Qi, M.; Wang, Y.; Pallan, P.; Owens, C.; Bui, J.; West, D.; et al. (American journal of transplantation, 2008)
This prospective phase 1/2 trial investigated the safety and reproducibility of allogeneic islet transplantation (Tx) in type I diabetic (T1DM) patients and tested a strategy to achieve insulin‐independence with lower islet mass. Ten C‐peptide negative T1DM subjects with hypoglycemic unawareness received 1–3 intraportal allogeneic islet Tx and were followed for 15 months. Four subjects (Group 1) received the Edmonton immunosuppression regimen (daclizumab, sirolimus, tacrolimus). Six subjects (Group 2) received the University of Illinois protocol (etanercept, exenatide and the Edmonton regimen). All subjects became insulin‐ independent. Group 1 received a mean total number of islets (EIN) of 1460 080 ± 418 330 in 2 (n = 2) or 3 (n = 2) Tx, whereas Group 2 became insulin‐ independent after 1 Tx (537 495 ± 190 968 EIN, p = 0.028). All Group 1 subjects remained insulin free through the follow‐up. Two Group 2 subjects resumed insulin: one after immunosuppression reduction during an infectious complication, the other with exenatide intolerance. HbA1c reached normal range in both groups (6.5 ± 0.6 at baseline to 5.6 ± 0.5 after 2–3 Tx in Group 1 vs. 7.8 ± 1.1 to 5.8 ± 0.3 after 1 Tx in Group 2). HYPO scores markedly decreased in both groups. Combined treatment of etanercept and exenatide improves islet graft function and facilitates achievement of insulin‐independence with less islets. Combined TNF‐alpha blockade and exenatide facilitates achieving insulin‐independence after allogeneic islet transplantation in brittle type I diabetic patients, but fails to show a measurable islet trophic effect and increase of functional islet mass over time.